Book Reviews. Issue 1 (1st June 2021) - Unknown
Abstract : George Robert Bateman, Jr., The Transformative Potential of Participatory Budgeting: Creating an Ideal Democracy. Garett Jones, 10% Less Democracy: Why You Should Trust Elites a Little More and the Masses a Little Less.